Determination of biogenic amines in alcoholic beverages using a novel fluorogenic compound as derivatizing reagent. Issue 32 (1st June 2021) - Zhu, Fangfang; Liu, Honglong; Zhang, Wenqing; Du, Chuanyuan; Zhu, Hao; Du, Xiaodi; Hu, Xiaosong; Lin, Yawei
Abstract : A novel fluorescent turn-on probe was synthesized and served as a pre-column derivatizing reagent for quantitative analysis of biogenic amines, then a method was established and used in their quantification in several alcoholic beverages. Abstract : Biogenic amines (BAs) are organic nitrogenous compounds that are responsible for several biological events. If their concentration reaches the threshold level, it can cause mild to serious health problems in human. A novel bis-styrylphenyl Meldrum's acid derivative (BSMAD) was synthesized and served as a fluorescent turn-on pre-column derivatizing reagent for the quantitative analysis of BAs. A method for the determination of BA by high-performance liquid chromatography (HPLC) was established, which has a low detection limit (0.4 nmol L −1 ), excellent linearity ( R 2 ≥ 0.9946) and repeatability (RSD ≤ 3.7% intra-day, RSD ≤ 5.8% inter-day). The proposed method was successfully applied for the determination of BAs in several alcoholic beverages, including yellow wine, red wine, cooking wine, and beer. Satisfactory recoveries were obtained in the range of 94.6–100.5%. Compared with other methods, this pre-column derivatization method using BSMAD is simple, reliable, highly sensitive, and of low interference, providing an effective method for future studies of BAs in different matrices.